Demographical, etiological and clinical characteristics of cases with cerebral palsy - Kabakuş, Nimet; Açik, Yasemin; Kurt, Abdullah; Özdiller, Didem Sükran; Aygün, A. Denizmen (My University, 2005)
It is known that there is a relation between clinical heterogeneity of cerebral palsy (CP) and demographical, etiological and clinical characteristics of the patients. In the present study, such characteristics of the patients were examined and relations between evitable/possible causes and prognosis were investigated. Of the 133 CP patients whom we followed between 1998 and 2003, 50 patients who had full records were retrospectively evaluated. The findings showed that multiple gestation, asphyxia and premature birth and low educational level of the parents were remarkable in a high rate of births with CP, and that malnutrition posed an additional problem in these cases. It was also determined that pathological signs in computerized tomography could be an unfavorable prognostic indicator of rough motor development (p<0.05). In line with these results, it can be said that improvement in maternal education and prevention of asphyxial and premature births can help prevent CP development. Treatment of malnutrition can be expected to improve the current situation.
Serebral palsili hastalarimizin demografik, etiyolojik ve klinik özellikleri
Keywords: Cerebral palsy; Child; Prognosis; Treatment